Mitigating CO2 emissions of concrete manufacturing through CO2-enabled binder reduction. (29th October 2019) - Lim, Tae; Ellis, Brian R; Skerlos, Steven J
Abstract: Past studies on CO2 utilization in the concrete industry have primarily focused on maximizing sequestered CO2, while focusing less on CO2 avoidance possible by reducing binder use through the addition of CO2 to concrete formulations. In this paper, we study the net CO2 reduction and cost benefits achievable by reducing binder loading while adding CO2 via three approaches: carbonation during curing, carbonation during mixing, or carbonation with recycled concrete aggregate. These techniques are evaluated for a cohort of concrete formulations representing the diverse mixture designs found in the US ready-mixed and precast industries. Each formulation is optimized for reduced binder loading where the use of CO2 directly in the formulation recovers the lost compressive strength from reduced binder. We show that over an order of magnitude more CO2 can be avoided when binder reduction is jointly implemented with CO2 utilization compared to utilizing CO2 alone. As a result, nearly 40% of the annual CO2 emissions from the US concrete industry could, in principle, be eliminated without relying on novel supplemental materials, alternative binder, or carbon capture and sequestration. The recently amended 45Q tax credit will not incentivize this strategy, as it only considers carbon sequestration. However, we find that the saved material cost from reduced binder use on its own may provide a significant economic incentive to promote the joint strategy in practice. We conclude that the real value of CO2 utilization in concrete hinges on exploiting CO2 -induced property changes to yield additional emission reduction, not by maximizing absorbed CO2 .